Fentanyl Induces Cerebellar Internal Granular Cell Layer Apoptosis in Healthy Newborn Pigs - Sabir, Hemmen; Dingley, John; Scull-Brown, Emma; Chakkarapani, Ela; Thoresen, Marianne (Frontiers in Neurology, 2018)
Background: Opioids like fentanyl are regularly used in neonates for analgesia and sedation. So far, they have been reported to be safe and eligible to use. The cerebellum has become a focus of neurodevelopmental research within the last years, as it is known to play an important role in long-lasting motor, cognitive and other behavioral changes. The cerebellar cortex is of major importance in the coordinative role of the cerebellum and highly vulnerable to injury and impaired growth. Objective: This study was performed to evaluate the apoptotic effect of intravenous fentanyl infusion on the cerebellum in healthy newborn pigs. Methods: Thirteen healthy pigs (<median 12 h old) were randomized into: (1) 24 h of intravenous fentanyl at normothermia (NTFe, n=6) or (2) non-ventilated controls at normothermia (NTCTR, n=7). Cerebellar sections were morphologically assessed after staining with Hematoxylin-Eosin. In addition, paired sections were immuno-stained for cell death (cleaved caspase-3 and TUNEL) and positive cells were counted in defined areas of the internal granular cell layer. In total, cells in three cerebellar gyri were counted. Results: We found that there was an increase in cells with apoptotic morphology in the internal granular cell layer in the NTFe group. For quantification, we found a significant increase in cell death in group (1) (median (range) number of caspase-3 positive cells group (1) 8 (1-22) vs. group (2) 1 (1-6) and TUNEL positive cells (1) 6 (1-10) vs. (2) 1 (0-4)). In both groups, there was no difference in the number of Purkinje cells. Both groups had comparable and stable physiological parameters throughout the 24h period. Conclusions: Twenty-four hours of continuous intravenous fentanyl infusion increased apoptosis in the internal granular cell layer in the cerebellum of healthy newborn pigs.